2018
DOI: 10.4067/s0716-10182018000300233
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiología y factores de riesgo de internación prolongada en niños con leucemia y bacteriemia. Estudio de cohorte

Abstract: Cuidados intermedios y moderados (JR, GG). Los autores declaran que no presentan conflictos de interés. El presenta estudio no tuvo fuente de financiamiento externa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…We observed that more than 90% of the patients in both groups had underlying diseases, being hematology and oncology diseases the most prevalent. In a cohort study conducted at our hospital, children with hematological disease and prolonged hospitalizations had a higher risk of bacteremia, with a predominance of gram-negative bacilli ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that more than 90% of the patients in both groups had underlying diseases, being hematology and oncology diseases the most prevalent. In a cohort study conducted at our hospital, children with hematological disease and prolonged hospitalizations had a higher risk of bacteremia, with a predominance of gram-negative bacilli ( 16 ).…”
Section: Discussionmentioning
confidence: 99%